Determination of Heavy Metal Concentrations in Some Fish Species Consumed in Karaman Province, Türkiye - Numan Emre Gümüş; Fuat Gökbel; Ziya Aydın (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
Heavy metals, with their ability to accumulate in the environment, can be transported to the aquatic ecosystem and to humans through fish consumption. Since they are not biodegradable, heavy metals have the potential to cause serious harm to human health. The insufficient aquaculture production of Karaman province has led to aquaculture products coming from different regions. No previous study has been conducted on the metal levels of fish species from different ecological regions in Karaman province. In 2023, the muscle metal bioaccumulations and the possible health effects of consumption of eight fish species (bogue (Boops boops), European seabass (Dicentrarchus labrax), European anchovy (Engraulis encrasicolus), red mullet (Mullus barbatus), rainbow trout (Oncorhynchus mykiss), red porgy (Pagrus pagrus), gilt-head seabream (Sparus aurata) and Mediterranean horse mackerel (Trachurus mediterraneus)) purchased from the local market were investigated in Karaman province. Metal concentrations (As, Cd, Cr, Cu, Fe, Mn, Ni and Zn) were determined by Inductively Coupled Plasma - Optical Emission spectroscopy (ICP-OES) and their levels were compared with the maximum permissible limits of national and international regulations. It was found that the mean concentrations of cadmium (Cd) in the Mediterranean horse mackerel (0.060 mg/kg), bogue (0.063 mg/kg) and red porgy (0.171 mg/kg), and the mean concentration of inorganic arsenic (iAs) in red porgy (0.233 mg/kg) exceeded the maximum permissible limits of the regulations. Health risk assessment methods (Estimated Daily Intake, Target Hazard Ratio, Hazard Index) have shown that the fish species examined are safe to consume.